HUMAN CAPITAL UNDER CRISIS: EVALUATION AND PRESERVATION OPPORTUNITIES SEARCH - О. Grishnova; S. Dmitruk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper estimates the impact of crisis on human capital. The elements of modern system crisis in Ukraine – socio-economic, political, military crisis are characterized. The directions of their negative impact on human capital are found. The system of crisis depth indicators and method of crisis depth integral index calculation is offered. Ukrainian system crisis of 2014-2015 is found as the deepest one in the country’s history of XXI century; it has dealt a devastating blow to reproduction capabilities of human capital. The impact assessment of crisis on integral index of human capital preservation is carried out in the system of statistical analysis STATISTICA 10. The results of evaluation prove that crisis mostly impacts on employment, social security and health care financing. The evidence reviles highly topicality of finding opportunities to reduce crisis negative impact on human capital preservation. The most important directions are: strengthening of social responsibility level of Ukrainian society, development of mutual aid culture, strengthening of the cohesion level and overcoming tendencies of individualization.